A study of the mortality trend of the Singapore population - Goh, Jio Young (2014)
To enable students to apply the knowledge and skills learnt in the University, the Final Year Project is implemented as one of the requirements for the fulfilment of the Bachelor of Business (Actuarial Science) degree. This undertaking enables undergraduate not only to integrate the knowledge learnt during the 3-year coursework but also to undertake independent study to solve various problem.